Effects of Surface Modification of Nanotube Arrays on the Performance of CdS Quantum-Dot-Sensitized Solar Cells - Danhong Li; Nengqian Pan; Jianjun Liao; Xiankun Cao; Shiwei Lin (International Journal of Photoenergy)
CdS-sensitized TiO2 nanotube arrays have been fabricated using the method of successive ionic layer adsorption and reaction and used as a photoanode for quantum-dot-sensitized solar cells. Before being coated with CdS, the surface of TiO2 nanotube arrays was treated with TiCl4, nitric acid (HNO3), potassium hydroxide (KOH), and methyltrimethoxysilane (MTMS), respectively, for the purpose of reducing the interface transfer resistance of quantum-dot-sensitized solar cells. The surfaces of the modified samples represented the characteristics of superhydrophilic and hydrophobic which directly affect the power conversion efficiency of the solar cells. The results showed that surface modification resulted in the reduction of the surface tension, which played a significant role in the connectivity of CdS and TiO2 nanotube arrays. In addition, the solar cells based on CdS/TiO2 electrode treated by HNO3 achieved a maximum power conversion efficiency of 0.17%, which was 42% higher than the reference sample without any modification.